Aprendizagem significativa de termodinâmica a partir da leitura da obra A volta ao mundo em 80 dias de Júlio Verner - Mazaro, Simone Bonora (2019)
The present text refers to an investigative study about significant learning of Thermodynamics from the reading of Jules Verne's work Around the World in 80 Days. The investigation is part of the research line "Theoretical-methodological Foundations for the teaching of Sciences and Mathematics", from the professional master's degree in Science and Mathematics Teaching, the Postgraduate Program in Teaching Science and Mathematics (PPGECM), in the University of Passo Fundo (UPF). It seeks a greater approximation between the contents of thermodynamics and experiential situations of students, since most of them consider physics difficult to comprehend, linked to methodologies far from the reality they are inserted. Joining Literature and Physics Teaching could be a way to awaken the interest and motivation of the learner because, according to Zanitic (2006), joining these two areas provides a more complete and effective learning of the world around one. The main objective of the study is to investigate the effectiveness of a didactic sequence of Thermodynamics for the promotion of meaningful learning from the literary work mentioned above. The problem lies in investigating the potential of this didactic sequence to promote meaningful learning. The proposal, based on the basic foundations of TAS, consists of three stages, which were structured in ten meetings and developed in a second-year high school class in a state public school in the city of Água Santa, RS. At each meeting, research instruments were applied to identify the subsumptions present in the students' cognitive structure, previous organizers to establish the link between previous knowledge and the subjects addressed and didactic strategies favoring the occurrence of targeted learning. The research is qualitative and participatory, and the proposal was evaluated based on the verification of two main aspects: Potentially Significant Material, through the logbook and the semi-structured interview, and Signs of Significant Learning, analyzing the material produced by the students (texts, drawings, maps, report of experimental activity). According to the results obtained, it is believed that the proposal reached the objectives, since the material produced can be considered potentially significant and favors the occurrence of signs of significant learning, since the students demonstrated to be able to relate the content with their previous knowledge, promoting the progressive differentiation and the integrative reconciliation of concepts and transposing content into different contexts. As an educational product, the work presented a supporting text covering contents related to thermodynamics and intended for high school teachers. This product is available on the website <https://educapes.capes.gov.br/handle/capes/431761>.